First Study in Men Evaluating a Surgical Robotic Tool Providing Autonomous Inner Ear Access for Cochlear Implantation - Topsakal, Vedat; Heuninck, Emilie; Matulic, Marco; Tekin, Ahmet M.; Mertens, Griet; Van Rompaey, Vincent; Galeazzi, Pablo; Zoka-Assadi, Masoud; van de Heyning, Paul (Frontiers in Neurology, 2022)
Image guided and robot assisted surgeries have found their applications in skull base surgery. Technological improvements in terms of accuracy also opened new opportunities for robotically assisted cochlear implantation surgery (RACIS). The HEARO® robotic system is an otological next-generation surgical robot to assist the surgeon. It firstly provides software-defined spatial boundaries for orientation and reference information to anatomical structures during otological and neurosurgical procedures. Secondly it executes a preplanned drill trajectory through the temporal bone. Here, we report how safe the HEARO procedure can provide an autonomous minimally invasive inner ear access and the efficiency of this access to subsequently insert the electrode array during cochlear implantation. In 22 out of 25 included patients, the surgeon was able to complete the HEARO® procedure. The dedicated planning software (OTOPLAN®) allowed the surgeon to reconstruct a three-dimensional representation of all relevant anatomical structures, designate the target on the cochlea, i.e. the round window, and plan the safest trajectory to reach it. This trajectory accommodated the safety distance to the critical structures while minimizing the insertion angles. A minimal distance of 0.4 and 0.3 mm was planned to facial nerve and chorda tympani respectively. Intraoperative cone-beam computed tomography supported safe passage for the 22 HEARO® procedures. The intraoperative accuracy analysis reported the following mean errors: 0.182 mm to target, 0.117 to facial nerve and 0.107 mm to chorda tympani. This study demonstrates that microsurgical robotic technology can be used in different anatomical variations, even including a case of inner ear anomalies, with the geometrically correct keyhole to access to the inner ear. Future perspectives in RACIS may focus on improving intraoperative imaging, automated segmentation and trajectory, robotic insertion with controlled speed, and haptic feedback. This study (EAR2OS and ARCI25) was registered at clinicaltrials.gov under identifier NCT03746613 and NCT04102215.